ANALISIS STRATEGI PENGEMBANGAN KREDIT UKM PADA KOPDIT CU KHATULISTIWA BAKTI KANTOR PELAYANAN KOTA BARU PONTIANAK - Imel Imel; F. Y. Khosmas; Okianna Okianna (Universitas Tanjungpura, 2020)
AbstractThis purpose of this study are to determine the strategy for developing SME loans at Service Office CU Khatulistiwa Bakti Kota Baru. The research method used in this research were descriptive with a qualitative research form. The data sources of this research were debtors, CUKB data and managers as well as questionnaire sheets as well as the results of interviews with the manager of Kopdit CU Khatulistiwa Bakti Kota Baru Service Office. The results showed that the strategic factors that influence the development of SME credit at service office Kopdit CU Khatulistiwa Bakti Kota Baru has the internal factors of strength strategy are procedures in granting credit with a score of (0.77) and the smallest score is the credit agreement system with a score of (0.40), the weakness of this strategy is the utility in conducting SME credit with a score (0.49) and the smallest score is the goal in conducting SME credit with a score (0.41). While the external factor of the opportunity strategy is the increase in funds with a score (0.60) and the smallest score is the development of assets with a score (0.42), the threat strategy is the SME debtor's target in doing credit with a score (0.27) and the smallest score is the accuracy of the debtor. in the deposit with a score (0.25).Keywords: Strategy, Credit, UKM, SWOT